Mobility Cultures in Megacities: results from a global study - Wulfhorst, G.; Kenworthy, Jeffrey; Kesselring, S.; Kuhnimhof, T.; Lanzendorf, M.; Priester, R. (WCTR, 2013)
Megacities worldwide show an important diversity not only in structural properties and mobility behavior but also in cultural values and public policies. Many common challenges of sustainable development culminate in the global hubs of economic growth, social disparity and environmental risks, especially those concerning transport. Is the approach of “mobility cultures” an appropriate framework to develop successful local strategies? The objective of the research presented has been to understand the diversity of mobility patterns and the underlying conditions in selected megacities worldwide, in order to support the development of policies for sustainable urban mobility. The paper is based on the results published in the book “Megacity Mobility Culture - How Cities Move on in a Diverse World”. Six clusters of megacities worldwide have been identified as non-motorized cities, paratransit cities, transit cities, auto cities, traffic saturated cities, and hybrid cities. The selected researchers have developed individual analyses on Atlanta, Los Angeles, Ahmadabad, Johannesburg, Shanghai, Sao Paolo, London, and Berlin. Every city is unique: this research shows the importance of specific local conditions to be taken in account for the development of sustainable policies of urban mobility. At the same time, every city seems to be “the same”: Comparable challenges worldwide and common systemic interdependencies between the local structure of transport supply and the built environment, public plans and programs, individual preferences and values as well as urban mobility behavior show that a mobility culture approach might be an appropriate frame workfor successful urban transport policies. Further cooperative research and networking is needed to exchange on experiences of good practice and to develop innovative solutions in a diverse world.